Hypoxia signaling in the equine small intestine: Expression and distribution of hypoxia inducible factors during experimental ischemia - Verhaar, Nicole; de Buhr, Nicole; von Köckritz-Blickwede, Maren; Dümmer, Katrin; Hewicker-Trautwein, Marion; Pfarrer, Christiane; Dengler, Franziska; Kästner, Sabine (Frontiers in Veterinary Science, 2023)
Hypoxia inducible factors (HIF) are widely researched in human medicine for their role in different disease processes. The aim of this study was to investigate the expression and distribution of HIF in experimental small intestinal ischemia in the horse. In 14 horses under general anesthesia, segmental jejunal ischemia with 90% reduction in blood flow was induced. The horses were randomly divided into two groups of 7 horses, one subjected to ischemic postconditioning (IPoC) by delayed reperfusion, and a control group (group C) undergoing undelayed reperfusion. Intestinal samples were taken pre-ischemia, after ischemia and after reperfusion. Following immunohistochemical staining for HIF1α and -2α, the immunoreactivity pattern in the small intestine was evaluated by light microscopy, and the mucosal enterocyte and muscularis staining were semi-quantitatively scored. Additionally, mucosal HIF1α protein levels were determined by an Enzyme Linked Immunosorbent Assay (ELISA), and mRNA levels of HIF1α and its target genes by a two-step real-time Reverse Transcriptase Polymerase Chain Reaction. Statistical comparison was performed between the groups and time points using parametric and non-parametric tests (p<0.05). All cell types exhibited cytoplasmic and nuclear immunoreactivity for HIF1α. After reperfusion, the cytoplasmic staining of the crypt and villus enterocytes as well as the villus nuclear staining significantly increased, whereas the perinuclear granules in the crypts decreased. The protein levels showed a significant decrease in group C at reperfusion, with lower HIF1α levels in group C compared to group IPoC during ischemia and reperfusion. No other group differences could be detected. In the HIF2α stained slides, mild to moderate cytoplasmic staining yet no nuclear immunoreactivity of the enterocytes was observed, and no significant changes over time were noted. In conclusion, the changes in HIF1α immunoreactivity pattern and expression over time suggest that this transcription factor plays a role in the intestinal response to ischemia in horses. However, the current study could not identify an effect of IPoC on HIF distribution or expression.